Use of Electronic Data and Existing Screening Tools to Identify Clinically Significant Obstructive Sleep Apnea - Carl A Severson; Sachin R Pendharkar; Paul E Ronksley; Willis H Tsai (Canadian Respiratory Journal)
OBJECTIVES: To assess the ability of electronic health data and existing screening tools to identify clinically significant obstructive sleep apnea (OSA), as defined by symptomatic or severe OSA.